2018
DOI: 10.1186/s12884-018-2058-9
|View full text |Cite
|
Sign up to set email alerts
|

Using a composite adherence tool to assess ART response and risk factors of poor adherence in pregnant and breastfeeding HIV-positive Cameroonian women at 6 and 12 months after initiating option B+

Abstract: BackgroundAntiretroviral therapy (ART) adherence in preventing HIV mother-to-child transmission in association with virological suppression and risk factors of low adherence in the Cameroon’s Option B+ programme are poorly understood. We used a composite adherence score (CAS) to determine adherence and risk factors of poor adherence in association with virological treatment response in HIV-positive pregnant and breastfeeding women who remained in care at 6 and 12 months after initiating ART.MethodsWe prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 34 publications
4
30
1
4
Order By: Relevance
“…Previous estimates of suboptimal ART adherence among pregnant WLWH in Cameroon were lower than reported in this study. A study of pregnant or breastfeeding WLWH in Cameroon found that 20% of study participants reported moderate ART adherence and 7% reported low ART adherence (measured using a four-item self-report questionnaire) six months after initiating Option B+ [ 42 ]. A study of PLWH (men and women) in Cameroon found that between 23% and 35% of participants reported recent non-adherence to ART regimens [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous estimates of suboptimal ART adherence among pregnant WLWH in Cameroon were lower than reported in this study. A study of pregnant or breastfeeding WLWH in Cameroon found that 20% of study participants reported moderate ART adherence and 7% reported low ART adherence (measured using a four-item self-report questionnaire) six months after initiating Option B+ [ 42 ]. A study of PLWH (men and women) in Cameroon found that between 23% and 35% of participants reported recent non-adherence to ART regimens [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…While these studies provide important information regarding the validity of self-reported measures, data are limited in Chinese PLHIV and comparison of those self-reported measures with long-term biological measures of adherence. In addition, some studies used a composite adherence score (CAS) from several self-reported measures with the hope to offset or reduce potential biases in self-reporting [27][28][29]. Several studies employed CAS measures to predict objective measures of adherence (e.g., device-based measures and viral load) [17,18,26], and did not find advantages over the individual self-reported measures.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that did not measure adherence as an outcome were excluded from the systematic review. Thirty-one journal articles met the inclusion criteria [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] and were included in the systematic review. Figure 1 shows the flowchart of the systematic review process.…”
Section: Resultsmentioning
confidence: 99%
“…The study designs consisted of ten cohort studies [ 24 , 25 , 29 , 33 , 34 , 37 , 38 , 47 , 52 , 53 ], four pre-post studies [ 26 , 28 , 35 , 36 ], sixteen randomized controlled trials [ 27 , 31 , 32 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 54 ], and only one cross-sectional study [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation